Surgical Management for a Rare Pedunculated Left Ventricular Apical Lipoma: A Case Report and Review of Literature - Song, Long; Iroegbu, Chukwuemeka Daniel; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Cardiac lipomas, though extremely rare, are encapsulated tumors composed primarily of mature fat cells. Despite their benign character, cardiac lipomas can cause life-threatening complications by rapid growth. Cardiac lipomas, which are frequently located in the left ventricle (LV) or right atrium, can originate either from the subendocardium, subpericardium, or the myocardium. They are usually asymptomatic and carry a good prognosis during long-term follow-up; however, published reports show that untreated cardiac lipomas may be fatal when they cause arrhythmic or obstructive symptoms. In addition, several surgical options have been reported to obtain an appropriate operative view following poor visualization, primarily when tumors are located in the LV. Herein, we present a case of a pedunculated LV apical lipoma in a symptomatic patient successfully managed by surgical resection. We also discuss diagnostic modalities in surgical planning and the choice of surgical approach.